Penyusunan Tolok Ukur Evaluasi Kinerja BUMN Berdasar Alternatif Pengelompokannya. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT Public enterprise has two dimensions. As a business enterprice, it has to be profitable and grows. As a public organization, it has to be public oriented.. Those two different interests could be in conflict with each other. however, It has to be kept in a balance, although it is difficult to be realized This paper tries to group the public enterprises that can be used in the formulation of .the performance criteria. By grouping them, it will simpler without reducing its uniqueness because of the differences in almost 200 public enterprises in Indonesia. The performance criteria Is stressed on the evaluation of management effectiveness. The paper also tries to identify the attidute of their executives on the objectives and the weight of the criteria by grouping them and to test how far the similarity of their the perceptions among them and the government official as focal point. Public enterprises could be grouped based on their product and consumer approach into 4 categories Groups I consists of public enterprises which goal has in distribution, Group II concetrate on infrastusture, Group 1ff has the task to accelerate economic development, and Group IV is acting more as a source of government revenue to finance economic development and improving the balance of payment. Refering to the executives responsibility on performance, our public enterprises can be grouped according to two approaches, namely the responsibility center and relative balance approach In relation to their public and business dimensins. Responsibility center approach consistsof profit center group, expenditur center, social responsibility center, and standart cost center group. Meanwhile, relative balance approach regarding public and business dimensions, which resulting a group that tends to be more public regulated by government and group that tends to be. more business oriented market mechanism. Using statistical inference, it can be concluded- that there is no significant difference in objectves and priority among the public groups with difference goals.. There is no correlationn between objectives priority and the weight of criteria on group that has goal of distribution and infrastucture. However, whitin the group that has goal of accelerating economic development and source of government revenue, there is a clear correlation between' objective priority and weight of criteria. Our study suggests that there is no significant difference in perception between the public enterprise executive and government official in determining objectves priority and the weight of criteria. This lack of difference may be caosed-by the fact that all are governed by the same regulation and all executive are evaluated on the same criteria. Formulating performance criteria by using stategic business. unit approach has resulted an evaluation formula for management effectiveness that can be used to evaluate all activities of each public enterprise taking into account commercial and non commercial performance and different government policy caused by the different market structure and supply condition.